Sistem Pendukung Keputusan Seleksi Calon Siswa Pelatihan Menggunakan Metode Saw Pada Balai Latihan Kerja Muaro Bungo - Agust Saputra, Edo; Roestam , Rusdianto (Jurnal Manajemen Sistem Informasi, 2023)
BLK is a government institution that provides free training to the community to improve the quality of human resources. In the running system there are obstacles in the process of selecting prospective students where parties must be able to select participants who are deemed worthy of training with specified criteria such as last education, age, economic background, and basic abilities of participants regarding the basic abilities of students. vocational they take through the results of the vocational examinations that are held. Based on these problems, a decision support system for the selection of training participants is needed so that it can assist BLK Muaro Bungo in producing accurate information so that it can be used in making education and training student admission selection decisions. The purpose of this study was to design a prototype for a student selection training decision support system using the SAW method and the UML system modeling tool. The result of this research is a prototype design of a decision support system for the student training selection process using SAW calculations so that it can become information that can be used in decision making by BLK Muaro Bungo.